Personality traits, psychosocial effects and quality of life of patients submitted to dental bleaching - Bonafé, Elize (BMC Oral Health, 2021)
BACKGROUND: Perception is defined as the ability to distinguish through the senses. All perception is dependent on factors such as personality, previously lived experiences and cultural elements. When planning an aesthetic treatment, consider the way the patients perceive the changes and outcomes is essential for reaching their expectations. The objective of this study was to assess if there was predominance of a personality trait of patient undergoing dental bleaching and if this treatment could promote changes in this traits, in the psychosocial impact and quality of life of these individuals. METHODS: The assessment of personality characteristics, quality of life, psychosocial and self-perception was a cross-sectional observational study and it was carried out by applying questionnaires to 55 patients that were submitted to a clinical phase. The psychometric instruments used were NEO FFI-R (personality), PIDAQ (psychosocial effect) and WHOQOL-BREF (quality of life). Each test domain was prior and after bleaching by Wilcoxon Signed Rank test (α = 0.05). The internal consistencies of each scale were evaluated by Cronbach's alpha. RESULTS: No statistical significant differences among personality traits means were observed among participants but there was predominance of two predominant personality traits in this study: conscientiousness (45.5%) and extraversion (34.5%). In four test domains of the PIDAQ, significant differences were observed before and after dental bleaching. The overall perception of the PIDAQ was also statistically significant demonstrating an improvement. There were no differences on overall or specific domains scores of the WHOQOL before and after treatment. CONCLUSIONS: Subjects who underwent dental treatment improved their self-confidence and reduced concerns about dental aesthetics, social and personality impact of dental alterations. TRIAL REGISTRATION: This study was conducted in parallel to a clinical investigation that aimed to evaluate tooth sensitivity related to dental bleaching technique and registered in REBEC clinical registry under protocol RBR-6pt2n3 in 13 November 2013.